2002
DOI: 10.1128/aac.46.5.1529-1534.2002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of (−)-Mefloquine Hydrochloride Reveals Consistency of Configuration with Biological Activity

Abstract: The absolute configuration of (؊)-mefloquine has been established as 11R,12S by X-ray crystallography of the hydrochloride salt, thus allowing comparison of the configuration of mefloquine's optical isomers to those of quinine and quinidine. (؊)-Mefloquine has the same stereochemistry as quinine, and (؉)-mefloquine has the same stereochemistry as quinidine. Since (؉)-mefloquine is more potent than (؊)-mefloquine in vitro against the D6 and W2 strains of Plasmodium falciparum and quinidine is more potent than q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
66
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 20 publications
14
66
0
1
Order By: Relevance
“…It is of note that, in contrast to threo CA, the racemate of 12, 11 threo MQ is as potent as the racemate of 12, 11 erythro mefloquine against Plasmodium berghei and P. falciparum in vitro (38,67). This difference reflects the increased ease of rotation around the link between the asymmetric carbon atoms due to the lower bulk of the piperidine ring as opposed to that of quinuclidine (36,67). The bulkier quinuclidine side chain of the CA may contribute to a loss of flexibility, imparting a structural constraint that may confer the greater stereospecificity of the CA than the other quinolines (19).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is of note that, in contrast to threo CA, the racemate of 12, 11 threo MQ is as potent as the racemate of 12, 11 erythro mefloquine against Plasmodium berghei and P. falciparum in vitro (38,67). This difference reflects the increased ease of rotation around the link between the asymmetric carbon atoms due to the lower bulk of the piperidine ring as opposed to that of quinuclidine (36,67). The bulkier quinuclidine side chain of the CA may contribute to a loss of flexibility, imparting a structural constraint that may confer the greater stereospecificity of the CA than the other quinolines (19).…”
Section: Discussionmentioning
confidence: 77%
“…1), also possess differential activities against P. falciparum. The (ϩ)-isomer of MQ, shown to be the stereo-equivalent of QD in terms of absolute conformation, reportedly has 1.7 to 1.8 times greater activity than (Ϫ)-MQ, the QN equivalent (36,38). We tested 106/1, 106/1 76I , and 106/1 76I-369F (Table 3) in drug assays to determine if the unusual effects of these PfCRT mutations on the CA was extended to the structurally similar MQ isomers.…”
Section: Among the Cq-resistant Mutants Pfcrt Hydropathy Is Correlatmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This first assignment was rejected and inverted by anomalous X-ray diffraction in 2002. 6 In 2008, however, a total synthesis using a proline-catalyzed asymmetric direct aldol reaction (recently reviewed for its broad applicability 7 ) and Beckmann rearrangement followed by a Mosher analysis 8 reconfirmed the original assignment. 9 Because these established methods for the determination of the absolute configuration, namely, anomalous diffraction and stereoselective synthesis, gave contrary results, we determined the absolute configuration using residual dipolar coupling (RDC)-enhanced NMR spectroscopy in combination with optical rotatory dispersion (ORD) and CD spectroscopy.…”
mentioning
confidence: 99%
“…The planar quinoline fragment and the piperidine ring, in a chair conformation with an equatorial alkyl substituent at C12, are rigid, 6 For the three torsion angles τ 1 , τ 2 , and τ 3 , the ROE spectroscopy (ROESY) cross-peaks (Scheme 1) indicated that there are preferred conformations that clearly distinguish between the two sides of the quinoline fragment relative to the substituent at C4: on the one hand, the strong ROEs between 5 and 11 and between 5 and 12ax, and on the other hand, the missing ROEs between 5 and 17eq and between 5 and 17ax (eq = equatorial, ax = axial). Additionally, the 3 J H11H12 = 2.7 Hz coupling and two strong 3 J HC heteronuclear multiplebond correlation (HMBC) signals ( 3 J H11C17 and 3 J H11C3 ) indicated preferred values of τ 1 and τ 2 .…”
mentioning
confidence: 99%